2021
DOI: 10.1155/2021/5965061
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Evaluation of Biological Activity of Lawsonia inermis Seeds Related to Alzheimer’s Disease

Abstract: Using Lawsonia inermis L. (henna) seeds has been frequently recommended for the improvement of memory in Iranian Traditional Medicine (ITM). In this respect, different fractions of the plant were prepared and evaluated for their in vitro biological assays related to Alzheimer’s disease (AD), including acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory activity as well as metal chelating ability and DPPH antioxidant activity. The dichloromethane and ethyl acetate fractions were able to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It has been depicted that single-target drug therapies have not offered an efficient therapeutic strategy for the treatment of AD and therefore, discovery of multi-target agents has been in the center of attention in the field of drug development research [5]. A variety of medicinal plants have been vastly applied for memory enhancement and other dementia-related complications via various mechanisms [6] such as ChE inhibitory activity [7][8][9][10], as well as prevention of neurodegenerative diseases [11].…”
Section: Open Accessmentioning
confidence: 99%
“…It has been depicted that single-target drug therapies have not offered an efficient therapeutic strategy for the treatment of AD and therefore, discovery of multi-target agents has been in the center of attention in the field of drug development research [5]. A variety of medicinal plants have been vastly applied for memory enhancement and other dementia-related complications via various mechanisms [6] such as ChE inhibitory activity [7][8][9][10], as well as prevention of neurodegenerative diseases [11].…”
Section: Open Accessmentioning
confidence: 99%
“…It was stated that the henna plant strengthens memory, relieves headache, and at the same time, henna plant oil relieves physical weakness and provides relief (Karaca & Şar, 2016; Semwal et al, 2014). Studies reported that henna reduces anxiety behaviours (Ahmed & Iqbal, 2014) and henna leaves are very important for the regulation of memory, attention, learning and motivation (Balaei‐Kahnamoei et al, 2021). It was thought that the characterization of medicinal plants as mental ointment could be used especially in the management of mental illnesses and could contribute to the practice of mental health nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical analysis confirmed the presence of β-sitosterol, 3-O-β-acetyloleanolic acid, betulinic acid, and oleanolic acid in dichloromethane and ethyl-acetate fractions of Lawsonia inermis (L.) seeds, which exhibited selective inhibitory action against BChE, with IC 50 values of 113.47 and 124.90 μg/mL, respectively, whereas ethyl-acetate and methanolic extracts displayed excellent antioxidant capacity, with IC 50 values of 3.08 μg/mL and 3.64 μg/mL, respectively [ 47 ]. Ferula ammoniacum , an endemic medicinal plant, has been reported to contain epigallocatechin gallate (EGCG), ellagic acid, quercetin, chlorogenic acid, phloroglucinol, mandelic acid, hydroxy benzoic acid, malic acid, rutin, and pyrogallol in different fractions.…”
Section: Plants and Their Bioactive Compounds In Averting The Pathoge...mentioning
confidence: 99%